2022
DOI: 10.1136/bmjpo-2021-001300
|View full text |Cite
|
Sign up to set email alerts
|

Early mobilisation and rehabilitation in the PICU: a UK survey

Abstract: ObjectiveTo understand the context and professional perspectives of delivering early rehabilitation and mobilisation (ERM) within UK paediatric intensive care units (PICUs).DesignA web-based survey administered from May 2019 to August 2019.SettingUK PICUs.ParticipantsA total of 124 staff from 26 PICUs participated, including 22 (18%) doctors, 34 (27%) nurses, 28 (23%) physiotherapists, 19 (15%) occupational therapists and 21 (17%) were other professionals.ResultsKey components of participants’ definitions of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 28 publications
2
15
1
Order By: Relevance
“…The questionnaire results show that the respondents have a positive viewpoint on early mobilisation and believe that early mobilisation can improve critically ill children's outcomes. These results are consistent with the results from earlier studies 9,17,21,26 . In our study and earlier studies, the most important barriers to early mobilisation are patient‐related factors: hemodynamic instability, the risk of dislocation of endotracheal tubes and vascular catheters and the level of sedation of the patient.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The questionnaire results show that the respondents have a positive viewpoint on early mobilisation and believe that early mobilisation can improve critically ill children's outcomes. These results are consistent with the results from earlier studies 9,17,21,26 . In our study and earlier studies, the most important barriers to early mobilisation are patient‐related factors: hemodynamic instability, the risk of dislocation of endotracheal tubes and vascular catheters and the level of sedation of the patient.…”
Section: Discussionsupporting
confidence: 93%
“…Yet, this was not ranked as an important barrier, whereas patient‐related factors were perceived as more important barriers. This contrasts with earlier studies that reported that PICU staff considered the lack of equipment, increased workload and the lack of practice guidelines to be significant barriers to early mobilisation 18,26,28,29 …”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Exercise principles can be exploited from the Physical Activity Guidelines for Americans 11 but beyond that, acute interventions are founded on clinical reasoning rather than the evidence base. The lack of a standardized protocol, inclusive of safe and defined activities, in paediatrics was seen as a barrier to rehabilitation delivery 12 . While protocols may support the delivery of early rehabilitation, flexibility and the independence to create individualized interventions are essential.…”
mentioning
confidence: 99%